Production Potential and Income of Very Small Farms in the European Union and Poland - Agnieszka STRZELECKA; Danuta ZAWADZKA (Communications of International Proceedings, 2020)
The primary goal of the paper is to assess the production potential and incomes of very small farms in the European Union, with particular emphasis on Polish entities. The basic source of data were statistics collected as part of the accountancy data collection system from agricultural holdings - European Farm Accountancy Data Network (European FADN). The analysis took into account the years 2012-2017. The spatial scope of the study covered the area of the European Union, with particular emphasis on Poland. Very small farms were distinguished based on the criterion of their economic size. It was assumed that a very small farm is one whose economic size does not exceed EUR 8,000 Standard Output (SO). The obtained results show that the value of assets of very small farms in Poland amounted to an average of around 73 thousand EUR in the analyzed period and was on average 66% higher than the value of assets used in the production process by very small agricultural holdings in the European Union (EU). At the same time, family farm income expressed per family labour unit (EUR / FWU) was almost 25% lower in very small farms in Poland than in the EU. It was also found that fixed assets dominate the assets structure of very small farms, and in the case of Polish entities this share amounted to 92.3% on average, while for EU farms the value of this ratio was slightly lower and amounted to 87.4%. The surveyed entities both in Poland and in the EU use primarily equity capital to finance agricultural activities. Furthermore, it was established that the relation of total production (total output) to total costs (total input) in the case of EU farms was higher than 1 throughout the entire analyzed period. On the other hand, very small farms from Poland from 2014 were characterized by a level of costs exceeding the value of production. This proves the importance of external support (in the form of operating subsidies) for creating agricultural income of very small farms in Poland.
Keywords: very small farm; family farm income; production potential; operating subsidies; FADN; Poland; European Union